Young Entrepreneur Transition to Youth NEET During Covid-19 Pandemic: Evidence from Indonesia - FX Gugus Febri Putranto; Devanto Shasta Pratomo; M Pudjihardjo (Jurnal Ekonomi dan Studi Pembangunan, 2023)
The global crisis caused by the pandemic also has an impact on the labor market in Indonesia. Young and women workers are strongly affected by the crisis and economic uncertainty due to the pandemic. One of the perceived impacts is the transition of young workers from entrepreneurs to NEET. This study aims to analyze the determinants of the transition of young entrepreneurs to NEET during the pandemic in Indonesia, both in general and gender-specific models. Data from the National Labor Force Survey (SAKERNAS) with individual panel observation in the period of August 2019 and August 2020 were analyzed using multinomial logistic regression. Important issues related to the determinants of the transition from an entrepreneur to NEET in Indonesia are demographic characteristics, COVID-19 risk status in the area of residence, and employment characteristics. Meanwhile, in the gender-specific model, there are differences in the determinants between male and female models. Prevention of the transition to NEET can be done by improving skills and education for young entrepreneurs, one of which is by expanding the scope of kartu prakerja. Specifically, on gender-based policy, women can be directed to the creative economy with flexible working hours